Insights into the role of energy source in hormesis through diauxic growth of bacteria in mixed cultivation systems. (December 2020) - Sun, Haoyu; Zhang, Xinyue; Wang, Dali; Lin, Zhifen
Abstract: Hormesis, a biphasic dose-response relationship characterized by low-dose stimulation and high-dose inhibition, has been reported to be closely related to energy sources in cultivation systems. However, few studies have clarified how the energy source influences hormesis. In this study, based on the typical diauxic patterns of Escherichia coli ( E. coli ) growth in mixed cultivation media containing 1.0 g L −1 glucose and Luria-Bertani broth, the hormetic response of sulfonamides (SAs) to E. coli growth was investigated under this diauxic growth condition to thoroughly explain the close relationship between hormesis and energy sources in cultivation systems. The results indicated that SAs trigger time-dependent hormetic effects on E. coli growth over the span of 24 h, in which the biphasic dose-response occurs only during the second lag and the earlier stage of the second log phase of diauxic growth. Mechanistic exploration reveals that SAs can bind with adenylate cyclase at a low dose and dihydropteroate synthase at a high dose, respectively, activating the stimulatory and inhibitory signaling pathway to influence carbon catabolite repression in diauxic growth, which can interfere with the metabolism of tryptone and yeast extract to ultimately trigger hormesis. Moreover, the stimulatory and inhibitory effects of SAs are changed by the variations in metabolic status at different growth phases, resulting in time-dependent hormesis. This study proposes an induced mechanistic explanation of hormesis in mixed cultivation media based on the energy source's metabolism, which may not only reflect the generalizability of hormesis but also further promote its application in production activities. Graphical abstract: Image 1 Highlights: E. coli growth presents diauxic pattern in 1.0 g L −1 Glc-added LB broth media. SAs induce time-dependent hormesis on E. coli under diauxic growth condition. SAs act on AC and DHPS to respectively induce stimulatory and inhibitory effects. These effects vary with metabolic status to result in time-dependent hormesis.